FACTORS OF INFLUENCE ON PAIN INTENSITY AND FUNCTIONAL ACTIVITY OF PATIENTS WITH BACK PAIN OF DIFFERENT LOCALIZATION - Maslova, I. G.; Mykhailovska, N. O.; Slobodin , T. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In order to identify the probable factors of the effect on the intensity of the pain syndrome and the parameters of the functioning of patients with back pain, depending on the location of the pain syndrome and concomitant pathology, 139 patients with non-specific back pain who were in inpatient treatment in the medical and sanitary part of JSC "Motor -Sich "with the first detected acute pain syndrome and acute exacerbation of chronic. The results of the study revealed a decrease in the level of physical functioning, deterioration of vital activity and the state of general and mental health (on the scale of SF-36) in patients with exacerbation of chronic pain, the lowest indicators of vital activity, social functioning, mental health and a high level of anxiety and depression - in patients with cervical and cranial localization of pain syndrome, despite the fact that patients with localized pain in the lower back are markedly higher levels of pain not only for YES, but also zg BP bottom axis scale SF-36. Patients with a combination of arterial hypertension and diabetes have been shown to have chronic pain syndrome.